Tamils beliefs and customs as found in an anthology of akananuru - the classical literature - Arulselvan Raju (2010)
Tamil literature is an ancient literature. It is also known as Cankam literature and classified as classical literature because from the earliest times it has not been expanded. This literature has a long history back to 3 A.D. Cankam literature as a classical literature included various anthologies and poems. The anthologies are Ettuttokai (Eight Anthology) and Pattuppattu (Ten Idylls) which contains more than two thousand poems. They are the main source of information to know about the Tamils history, their social life, economy activities, games, custom, beliefs, wars and religion. The purpose of this paper is to discuss about Tamils beliefs and customs during classical period as seen in Akananuru work. The discussion will use the anthology of Akananuru as main source with cankam poems as cross reference and will compare it with current one.